Zirconia: Substitute for Metal Ceramics - Kumar, C Gyan; Shruthi, DP; Raj, K Sounder; Kalpana, D; Harish, G (Journal of Orofacial Research, 2014)
In the search for the ultimate esthetic restorative material, many all-ceramic systems have been proposed. Dental research is nowadays directed toward metal-free prosthetic restorations in order to improve an esthetical outcome of crown and bridge restorations. Zirconia is a polycrystalline ceramic without a glassy phase and exists in several forms. Zirconia cores for fixed partial dentures (FPD) on anterior and posterior teeth and on implants are now available. This article is a review of zirconia crowns as replacement for conventional metal-ceramic crowns.